A Philosophical Analysis of Islamic Legal Principles in the Era of Modernity - Materan Materan (Journal of Mandalika Social Science, 2026)
This study provides a philosophical analysis of Islamic legal principles in the era of modernity, focusing on their relevance and application in contemporary societal contexts. Employing a qualitative research methodology through a literature study and library research, the paper examines key concepts within Islamic law—such as justice, equality, freedom, and human rights—while comparing them with modern legal frameworks. The findings reveal both alignment and tension between traditional Islamic jurisprudence and modern legal systems. While there is common ground in principles such as justice and human dignity, significant differences arise in areas such as gender equality, individual freedoms, and the application of human rights. The study highlights the role of ijtihad (independent legal reasoning) as a tool for adapting Islamic legal thought to contemporary issues. However, challenges remain in reconciling Islamic law’s traditional interpretations with the demands of modern governance, especially in contexts where secular legal systems prioritize individual rights over collective moral obligations. This research contributes to the ongoing discourse on the adaptability of Islamic law in modern times and suggests avenues for future research, including exploring the practical applications of ijtihad in modern legal systems and further investigating the interpretation of gender equality within Islamic jurisprudence.